The changing landscape of long-term share-based compensation in South Africa: an investigation into recent developments in employee incentive used by companies listed on the Johannesburg Stock Exchange - Mavrodinov, Nikolay Stefanov (Department of Finance and Tax, 2015)
Includes abstract.